PENERAPAN DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN UMKM KULINER “COBEK BAKAR SURABAYA” DI KEDUNGDORO - Naufal Safarel; Irra Chrisyanti Dewi (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the implementation of digital marketing in the culinary MSME Cobek Bakar Surabaya in Kedungdoro, Surabaya, with a focus on the digital marketing strategies implemented, the challenges faced, and their impact on sales and brand awareness. Digital marketing is an important strategy for MSMEs to increase competitiveness amidst the rapid development of the digital economy. The research method used is a qualitative approach with a case study design, with data collection techniques in the form of in-depth interviews, observation, and documentation. The research informants consisted of the owner, marketing staff, and consumers of Cobek Bakar Surabaya. The results show that the implementation of digital marketing is still in the basic stage, with a focus on social media as the main promotional channel. However, interaction with consumers and the use of e-commerce platforms are still limited, and there are challenges in terms of limited human resources and knowledge about advanced digital marketing. This study is expected to provide theoretical contributions to the development of digital marketing literature for culinary MSMEs, as well as provide practical recommendations for Cobek Bakar Surabaya and other MSMEs in optimizing the implementation of digital marketing to increase sales and brand awareness.